Treatment of cadmium-contaminated soil using ground granulated blastfurnace slag - Choy, Lennard Ren Jie (Nanyang Technological University, 2020)
There is a growing interest in the use of ground granulated blastfurnace slag (GGBS) and lime to treat soils, but the studies on using them to treat contaminated soils are insufficient. In this study, lime-activated GGBS is used to investigate the stabilization/solidification efficiency of this binder in treating cadmium (Cd)-contaminated soils. The properties of lime-GGBS treated-Cd contaminated soils were investigated with several laboratory tests, including the unconfined compressive strength (UCS), leachability, X-ray diffraction (XRD) and scanning electronic microscope (SEM). It was found that higher levels of lime content aided in increasing the strength of the soil. At both concentrations of Cd (8000 and 16000 ppm), the maximum strength of soils was still yet to be found as there was only increasing trends in strength. Soils with higher levels of Cd concentration yielded lower strength. Longer curing time showed higher UCS values as there was a longer hydration period. Leachate pH values increased with the increase of lime contents for soils. Higher lime contents and longer curing time decreased the leachability of Cd in the soils with different levels of Cd. Leachability was observed to be related to the pH of leachate, and the increase of pH showed a decrease in leachability. The XRD results illustrated that CSH and Cd(OH)2 were present in Cd-contaminated soils treated by lime-activated GGBS. The formation of these two minerals lowered Cd leachability in lime-GGBS treated-Cd contaminated soil. The formation of CSH was confirmed by the SEM results.